2018
DOI: 10.1016/j.bjorl.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The maturation state of the auditory nerve and brainstem in rats exposed to lead acetate and supplemented with ferrous sulfate

Abstract: This study indicate that the lead acetate can have deleterious effects on the maturation of the auditory nerve and brainstem (cochlear nucleus region), as detected by the Brainstem Auditory Evoked Potentials, and the ferrous sulphate can partially amend this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It was found that the administration of both synthetic and natural antioxidants has impressive effects on the prevention of metal-induced biochemical alterations, but the numbers of clinical studies in this field are still limited. For this purpose, Zucki et al [ 184 ] investigated the auditory system and its maturation, particularly the auditory nerve and brainstem, in rats that were exposed to lead acetate and supplemented with ferrous sulfate as an antioxidant agent. In this study, 15 male rats were exposed to 100 mg/L of lead acetate with ferrous sulfate (20 mg/kg), and 15 rats were exposed to 400 mg/L of lead with ferrous sulfate (20 mg/kg) within their drinking water for 6 weeks.…”
Section: Role Of Antioxidant Materials In the Tissue Regeneration Pro...mentioning
confidence: 99%
“…It was found that the administration of both synthetic and natural antioxidants has impressive effects on the prevention of metal-induced biochemical alterations, but the numbers of clinical studies in this field are still limited. For this purpose, Zucki et al [ 184 ] investigated the auditory system and its maturation, particularly the auditory nerve and brainstem, in rats that were exposed to lead acetate and supplemented with ferrous sulfate as an antioxidant agent. In this study, 15 male rats were exposed to 100 mg/L of lead acetate with ferrous sulfate (20 mg/kg), and 15 rats were exposed to 400 mg/L of lead with ferrous sulfate (20 mg/kg) within their drinking water for 6 weeks.…”
Section: Role Of Antioxidant Materials In the Tissue Regeneration Pro...mentioning
confidence: 99%